2004
DOI: 10.1111/j.1365-2109.2004.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of ammonia and its sub-lethal effects on selected haematological and enzymatic parameters of mrigal, Cirrhinus mrigala (Hamilton)

Abstract: A comprehensive acute toxicity trial was conducted using a static water system to study the toxic effect of ammonia on haematology and enzyme profiles of Cirrhinus mrigala H. The LC50 of total ammonia‐nitrogen (TAN) was 11.8 mg L−1 TAN (1.029 mg L−1 NH3‐N). The sub‐lethal test revealed that with increasing concentration of TAN, the total erythrocyte counts were reduced in lower concentrations (1–4 mg L−1 TAN) followed by higher levels in fish exposed to higher concentrations (8–16 mg L−1 TAN). In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 29 publications
7
77
0
1
Order By: Relevance
“…In addition, reduction in the activity levels of respiratory enzymes such as LDH and ADH and the depletion in the level of consumed oxygen could all have contributed to the observed behaviour and eventual mortality. This phenomenon was supported by the investigations of Lusková et al (2002) and Das et al (2004). Ceron et al (1997) had earlier reported a reduction in lactate concentration when fish were exposed to Diazinon at acute concentrations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, reduction in the activity levels of respiratory enzymes such as LDH and ADH and the depletion in the level of consumed oxygen could all have contributed to the observed behaviour and eventual mortality. This phenomenon was supported by the investigations of Lusková et al (2002) and Das et al (2004). Ceron et al (1997) had earlier reported a reduction in lactate concentration when fish were exposed to Diazinon at acute concentrations.…”
Section: Discussionsupporting
confidence: 70%
“…The decrease in oxygen consumption rate observed could have implication on the subsequent reduced LDH activity. The inhibition of these enzymes would result in the accumulation of metabolic intermediates in the liver therefore causing physiological stress in fish, which eventually lead to mortality if exposure is prolonged as suggested by Das et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in waterborne NH 3 concentration results in decreased diffusion, causing an increase in internal NH 3 that leads to re-establishment of the NH 4 + /NH 3 -equilibrium inside the fish. Das et al (2004) confirmed that a relatively small increase in waterborne NH 3 may cause a large increase in internal ammonia concentration, affecting some physiological functions, for instance diminishing the action of acetylcholinesterase in the brain and liver and reducing levels of hemoglobin and plasma proteins. As a consequence of the cumulative increase in plasma ammonia, some other physiological process could be disturbed, for example pH maintenance, electrolyte balance and general homeostasis (Tomasso, 1994).…”
Section: Discussionmentioning
confidence: 63%
“…The permeability of plasma membranes to uncharged and lipid-soluble NH 3 is higher than to NH 4 + ; therefore NH 3 is considered to be the most toxic form of ammonia (Das et al, 2004). An increase in waterborne NH 3 concentration results in decreased diffusion, causing an increase in internal NH 3 that leads to re-establishment of the NH 4 + /NH 3 -equilibrium inside the fish.…”
Section: Discussionmentioning
confidence: 99%
“…These contaminants which are obtained from the aquatic environment and food cover a wide spectrum of gases, chemicals and solids. Most toxicological studies have been limited to the effects of lethal or acute doses of these pollutants (Martinez & Souza 2002, Huertas et al 2002, Das et al 2004a, whereas, subtle physiological disorders result with exposure to sub-lethal/low doses of toxicants (Das et al 2004b,Varo et al 2007, Kori-Siakpere et al 2011. Various workers have reported histopathological changes in fish organs (e.g.…”
Section: Introductionmentioning
confidence: 99%